Sirtuin1 Suppresses Calcium Oxalate Nephropathy via Inhibition of Renal Proximal Tubular Cell Ferroptosis Through PGC‐1α‐mediated Transcriptional Coactivation - Chen Duan; Bo Li; Haoran Liu; Yangjun Zhang; Xiangyang Yao; Kai Liu; Xiaoliang Wu; Xiongmin Mao; Huahui Wu; Zhenzhen Xu; Yahua Zhong; Zhiquan Hu; et al. (Advanced Science)
Abstract Calcium oxalate (CaOx) crystals induce renal tubular epithelial cell injury and subsequent nephropathy. However, the underlying mechanisms remain unclear. In the present study, single‐cell transcriptome sequencing is performed on kidney samples from mice with CaOx nephrocalcinosis. Renal proximal tubular cells are identified as the most severely damaged cell population and are accompanied by elevated ferroptosis. Further studies demonstrated that sirtuin1 (Sirt1) effectively reduced ferroptosis and CaOx crystal‐induced kidney injury in a glutathione peroxidase 4 (GPX4)‐dependent manner. Mechanistically, Sirt1 relies on peroxisome proliferator‐activated receptor gamma coactivator 1α (PGC‐1α) to promote resistance to ferroptosis in the tubular epithelium, and PGC‐1α can recruit nuclear factor erythroid 2‐related factor 2 (NRF2) to the promoter region of GPX4 and co‐activate GPX4 transcription. This work provides new insight into the mechanism of CaOx crystal‐induced kidney injury and identifies Sirt1 and PGC‐1α as potential preventative and therapeutic targets for crystal nephropathies.